Product market competition, idiosyncratic and systematic volatility - Abdoh, Hussein; Varela, Oscar (Journal of Corporate Finance, 2017)
This study finds that competition increases idiosyncratic volatility relative to systematic volatility. Market power facilitates passing on firm specific cost shocks to customers but is irrelevant to passing on market cost shocks. A firm's competitive advantage in an industry is also more affected by changes in firm specific costs when there are many rivals. The results are robust to significant reductions in import tariff rates that reduce market power and consistent with lower pairwise returns' correlations following such events.